Risk management practices and performance of microfinancing banks in Malaysia / Roseziahazni Abdul Ghani and Rosli Mahmood - Abdul Ghani, Roseziahazni; Mahmood, Rosli (2015)
The purpose of this study is to investigate the state of risk management practices (RMPs) implemented among the microfinance providers in Malaysia and its relationship with the financial performance. By taking seven banking institutions and three developments financial institutions which participate in the micro financing initiative name as pembiayaan micro, the risk management practices were investigated. This study employed the measures available in the existing literature to measure the variables and is modified to match with the respondents. A total number of 1355 survey questionnaires were distributed to the branch managers through mail and 190 usable responses were received from the respondents The result reveals that only three dimensions of RMPs have significant relationship with the performance of financial institutions namely risk identification, risk monitoring and credit risk analysis. While, there is no relationship between risk management understanding and risk assessment and analysis and performance of financial institutions. The results also provide support that the supervision of risk management and internal control systems of Malaysian banks conform to internationally accepted standards that stipulated under Basel II.